2015
DOI: 10.3748/wjg.v21.i48.13548
|View full text |Cite
|
Sign up to set email alerts
|

First-line eradication forHelicobacter pylori-positive gastritis by esomeprazole-based triple therapy is influenced byCYP2C19genotype

Abstract: The results from this study suggest that there is no advantage to EPZ-based triple therapy on H. pylori eradication compared to other first-generation PPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
0
22
1
Order By: Relevance
“…When these patients had their doses escalated, H. pylori eradication rate increased to about 80% [70], supporting the need for escalated doses in CYP2C19 NM phenotypes. Contrary to the results by Saito et al [62], that found significant effect of  CYP2C19  genotype on H.pylori eradication in esomeprazole Schwab et al [71] did not document an effect for CYP2C19 genotype on GERD healing in a relatively large cohort of European patients (N = 205) who used esomeprazole. It is important to note that the study by Schwab et al was conducted before the discovery of *17 , and therefore *17 allele, which is present in 30% of patients with European ancestry was not assessed.…”
Section: Cyp2c19 and Ppi Pharmacogeneticscontrasting
confidence: 57%
See 3 more Smart Citations
“…When these patients had their doses escalated, H. pylori eradication rate increased to about 80% [70], supporting the need for escalated doses in CYP2C19 NM phenotypes. Contrary to the results by Saito et al [62], that found significant effect of  CYP2C19  genotype on H.pylori eradication in esomeprazole Schwab et al [71] did not document an effect for CYP2C19 genotype on GERD healing in a relatively large cohort of European patients (N = 205) who used esomeprazole. It is important to note that the study by Schwab et al was conducted before the discovery of *17 , and therefore *17 allele, which is present in 30% of patients with European ancestry was not assessed.…”
Section: Cyp2c19 and Ppi Pharmacogeneticscontrasting
confidence: 57%
“…Collectively, the data support better outcomes in management of GERD and higher success rate of H. pylori eradication in IM and PM phenotypes compared to NM, RM, and UM phenotypes (Table 4) [59,60,6264], which is consistent with the higher intragastric pH achieved in patients with reduced CYP2C19 activity and higher PPI concentrations [7779]. While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80].…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 71%
See 2 more Smart Citations
“…The eradication rate using traditional first-line therapy is low (70%) due to the increase in CLR resistance 11,17,18. 14 The Japanese government insurance has allowed first-line (PPI-AMX-CLR) and second-line (PPI-AMX-MTZ) eradication therapy.…”
mentioning
confidence: 99%